Food Safety on the Farm: Good Agricultural Practices and Good Handling Practices – Field Sanitation - Alexandra Chang; Renée M. Goodrich-Schneider; Keith R. Schneider (EDIS)
This is part of the Food Safety on the Farm series, a collection that reviews the generally recognized principles of GAPs as they relate to produce, primarily at the farm level and with particular focus on fresh Florida crops and practices. This publication focuses on GAPs relating specifically to field sanitation. Written by Keith R. Schneider, Renée M. Goodrich-Schneider, and Alexandra Chang, and published by the UF Department of Food Science and Human Nutrition, March 2012.